(untitled) (Progressive Agriculture, 2021)
Seaweed culture provides financial benefits and creates employment opportunity for coastal inhabitants of Bangladesh. This study was conducted to assess profitability and to determine the socioeconomic factors that affect the profitability of seaweed culture in the coastal region. Primary data were collected from 33 seaweed farmers for the study. The data were collected during the period of March 15 to March 31, 2018 through direct interviews and observation using a semi structured questionnaire and a check list. Both tabular and functional analyses were used to achieve the objectives of the study. It is evident from the study that seaweed culture is a profitable business. The total per square-meter cost of seaweed production was Tk. 1520 with a gross return of Tk. 2801.4 and net return was estimated at Tk. 1281.4 with a Benefit-Cost Ratio (BCR) 1.82. To estimate the contribution of different inputs on seaweed production through Cobb-Douglas production function, the explanatory variables considered were: bamboo cost, rope cost, human labour cost, repairing cost, age, experience, training, education and number of family members. Among these variables, labour and training were found positively significant at 1 percent level of significance with the regression coefficient of 0.209 and 0.556, respectively. This indicates that seaweed culture might be brought economic benefits of the community if they received more training and employ more labour. Therefore, policy should be focused on creating appropriate training arrangement and skilled labour to the coastal community for getting higher benefit. Seaweed farmers think that seaweed culture can be adopted as an alternative livelihood option if the government and other stakeholders help them with necessary supports for seaweed culture. Progressive Agriculture 31 (3): 227-234, 2020